Twenty Years of Airport Efficiency – A Bibliometric Analysis - Javier Cifuentes-Faura; Ursula Faura-Martínez (Promet - Traffic&Transportation, 2021)
This paper analyses the scientific study on airport efficiency in the WoS (Web of Science) database for the period 2000–2019. Productivity indicators have been obtained by author, years, journals, and institutions, and an analysis of visibility, impact, and scientific collaboration through co-citations was performed. The areas of greatest application are transport, engineering, and economics. This study reveals the existence of three research lines, one on airport safety and management, another on technical efficiency using mainly the DEA method, and the third associated with airport regularization issues. An important issue which is increasingly taken into account in efficiency studies is related to environmental aspects. In the ranking of journals publishing on airport efficiency, ordered by number of articles indexed in WoS, Journal of Air Transport Management is the one with the highest number of cited articles and publications, whereas Sustainability stands out as the first non-specific journal on transport. The University of Lisbon and the University of British Columbia are the ones that deal most with airport efficiency.